Necesidad de incluir un numeral al art. 110 del código civil estableciendo como causal de divorcio la violencia intrafamiliar - Moncayo Soria, Elisa Paulina (2015)
We are all aware that marriage is a civil and social reality, and when not working, law, has no choice but to admit this being useless and even harmful, any other legal solution that claims to artificially maintain an impossible coexistence, as although the marital union is in normal conditions, maintenance and balancing personal relationships between spouses, the imbalance in these relationships or outright violation of the obligations imposed on each create an abnormal situation that probably two distressed beings feel embittered their lives and this fact appears as a solution, divorce. Traditional and inexhaustible anti-divorce-divorce and debates have been displaced in time, because almost all legislation on the subject support the divorce. Thus, we see that the discussion of the issue in terms of legislation arises in adopting one or both other systems prevailing in the universal law: Divorce sanction and remedy divorce. Determining which events should serve as a basis for divorce is something that is very closely linked to the concept that the same is taken. In the so-called divorce sanction those events involving serious breaches of the arising of the marital relationship, which are especially abandonment, adultery, domestic violence and other sought. We talk about domestic violence when a person tries to control and exercise power over your partner in the context of a relationship. Physical, emotional, sexual or financial: different types of abuse can occur. In most cases, the perpetrators are men and the victim’s women. Any woman in any home may be affected by domestic violence. The wives have been subjected to abusive husband. Gender violence is major injustices that occur in our modern society they call must be added sex discrimination in political, family and society. Some wives keep this hell on earth, because unfortunately there are alternative to the situation. They are not prepared, mentally, financially, and socially to confront the situation and get away from her violent husband. There are cases where domestic violence is exercised wives, who even made more subtly, also become the husband's life a living hell. Marital infidelities, waste or economic pressures, neglect or maternal marital obligations, emotional blackmail, etc. are similar to those of shock or abuse of psychological damage. Sometimes women are not separated and suffer in silence for fear of losing their economic security and that of their children. This happens mostly in women who have no education. Sometimes not separate due to threats of further violence or death: "If you say anything to the police I'll kill you". If some women why they endured abuse for years he asks, the most common answer is: "For my children, not wanting to grow up without a father." Seems a valid answer, but if we analyze discover its inconsistency. In a situation of violence the children also suffer. Growing up in an atmosphere of tension and terror negatively affect their emotional development and later school dropout, drugs, psychological disorders, violence and crime. Worse repeatedly abused women, their individual identity are destroyed psychologically. That's incapacitates make correct decisions. Falls into the emotional ambivalence ("What good is it if not hit me!"); self-esteem drops to the floors to believe that deserves such insults and blows. His capacity of decision is void because the vital principle is mortally wounded. If such a person crushed he is threatened with "If I complaints, I'll kill you", you will feel paralyzed. Perhaps in a last attempt at survival react, but will do so with the same weapons. Spousal or domestic violence, as well as being a result of an imbalance of power between individuals, is also a serious public health problem, as well as violation of human rights of those who live with it, usually women. However, this form of abuse is almost always exercised on the part of men towards women or, more specifically, of whom, according to social rules, must be the protector not only of his girlfriend, but the rest of the family members. From this point of view, the issue of permanence of the family, can provide a slit through which to look at the problem of divorce, current and notorious relevance in the national debate topic, and the dissolution of certain familial forms for give way to others